Kalam Khobari and Kalam Insha’ Ghayr Talabi: A Comparative Analysis Based on Dilalah, Qasd, and Pragmatic Function in Arabic Rhetoric - Muhamad Imam Juyat Miko; Muhammad Rido'i (Journal of Practice Learning and Educational Development, 2026)
An accurate understanding of the classification of sentences into Kalam Khobari (declarative sentences) and Kalam Insha’ (non-declarative sentences) serves as a crucial foundation for mastering Ilmu Ma’ani, a vital pillar of Arabic Balaghah (rhetoric). However, in educational practice, confusion often arises—particularly when distinguishing Kalam Insha’ Ghairu Thalabi (non-imperative Insha’) from Kalam Khobari—due to apparent similarities in grammatical structure (Jum’ah: 2005; Al-Hasyimi: 1999). This study addresses this issue by examining the fundamental differences between the two. It employs a qualitative method utilizing a library research approach. The data analysis technique applied is descriptive-analytical and comparative-explanatory, drawing upon primary sources—such as classical and contemporary Balaghah texts—as well as supporting secondary sources. The analysis reveals that the fundamental distinction between Kalam Khobari and Kalam Insha’ Ghairu Thalabi lies in three key aspects. First, the Dilalah (semantic indication) aspect: Khobari involves a referential relationship (nisbah kharijiyyah) that exists prior to utterance, whereas Insha’ brings that meaning into existence or constructs it at the moment of utterance. Second, the Qasd (speaker's intention) aspect: A Khobari speaker intends to align their speech with reality or deviate from it, whereas a speaker of Insha’ aims to express a psychological state or create a new reality (such as commands, prohibitions, praise or condemnation, and contractual agreements). Third, the pragmatic function aspect: Khobari serves an informative function and is subject to truth-value assessment (shidq or kadzb), whereas Kalam Insha’ Ghairu Thalabi serves an expressive-performative function and is immune to true-false evaluation. The study concludes that understanding this triad of distinctions—dilalah, qasd, and pragmatic function—is the key to accurately distinguishing between these two types of sentences. This analysis not only provides conceptual clarity but also reveals the dimension of aesthetic beauty (jamaliyyah) inherent in the performative nature of Arabic within Kalam Insha’ Ghayr Talabi—an area that often poses difficulties for beginners.